Математична модель розширення оглядовості електричних мереж, які частково оснащені засобами телеметрії - Данилюк, О. В.; Дьяченко, С. В.; Саєвич, Р. В.; Міркевич, Я. Д. (Видавництво Національного університету «Львівська політехніка», 2007)
The mathematical model and algorithm of expansion of observability of electric network with partial remote control represented in this article. Application of such approach promotes quality of decision of task of state estimation electric network mode.